Reorganising the front line: the case of public call centre services. (1st October 2008) - Annika Schönauer
Abstract : The aim of this article is to examine a specific aspect of restructuring in the public sector: the implementation of call centres in customer service and its effects on job quality. The general trend towards organising customer services through call centres gained worldwide importance in the 1990s, but in the public sector it has emerged relatively recently in connection with strategies of 'new public management'. This article presents five international case studies from the public sector that exhibit different forms of restructuring. They range from internal reorganisation and the establishment of a public-private partnership to the full outsourcing of telephone-based customer services. The article concludes that, despite national differences, the introduction of call centres into the public sector, especially when combined with outsourcing, has dramatic impact on the quality of employment, especially in relation to three aspects: forms of employment, skills and know-how and interest representation.